Tax Planning Melalui Penerapan Zakat Sebagai Upaya Meminimalisir Beban Pajak Badan (Studi Kasus Pada PT. Wonojati Wijoyo, Kediri) - Puji Rahayu (Universitas Muhammadiyah Ponorogo, 2017)
Implementation of tax planning through tax lawdengan exploiting loopholes in tax regulations one of which is exempted from the tax object is the payment of zakat on the amil zakat or amil zakat institutions established or endorsed by the government. Zakat is part of the pillar of Islam is the third pillar. For the Islamic ummah zakat law it must be done.Manajemen company has done tax planning in minimizing the tax burden.How that has been used by companies through depreciation of assets and financing the procurement of goods using leasing or leasing services.Namun companies have never applied zakat payments As a tax savings. The purpose of this study to know the tax planning through the implementation of zakat as an effort to minimize the agency tax burden.Types of data used in this study are qualitative and quantitative data.Data in this study are taken directly in the form of data about corporate organizational structure, employee data, company history and tax planning system that has been applied company. The data analysis technique used in this research is qualitative descriptive by analyzing fiscal reconciliation in order to calculate the Corporate Income Tax by applying the company before applying the tax planning through the payment of zakat, calculating the amount of zakat, calculating the Income Tax after applying the tax planning through zakat payment, Comparing the Income Taxes owed before After applying the tax planning through the payment of zakat.From the research result, it is concluded that the income tax burden payable by the company in 2016 before doing the implementation of tax planning through the payment of zakat amounting to Rp 282.355.625, - while after implementing the zakat of Rp 275.449.750, - the difference of Rp 6.905.875, - And tax payable prior to the fiscal reconciliation of Rp 275,096,375,-. There is a difference of Rp 353,375, - so the researcher recommends to apply zakat payment to amil zalcat or amil zalcat institution which has been legalized by the government because it has been legalized by taxation and paying zakat besides being able to clean the property is also a mandatory command of Allah SWT We carry out according to His word in the Al-Qur'an.